2014
DOI: 10.1007/jhep10(2014)090
|View full text |Cite
|
Sign up to set email alerts
|

Localization in supergravity and quantum AdS 4 /CFT3 holography

Abstract: Abstract:We compute the quantum gravity partition function of M-theory on AdS 4 ×X 7 by using localization techniques in four-dimensional gauged supergravity obtained by a consistent truncation on the Sasaki-Einstein manifold X 7 . The supergravity path integral reduces to a finite dimensional integral over two collective coordinates that parametrize the localizing instanton solutions. The renormalized action of the off-shell instanton solutions depends linearly and holomorphically on the "square root" prepote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Although it has been demonstrated that (1.1) can be reproduced by the supergravity localization [15], we wish, in particular, to show that the emergence of the Airy function is not all due to the sophistications of supergravity and extra dimensions but rather lies at the core of 4d quantum gravity. Motivated by the appearance of Airy functions in quantum cosmology [16,17], we study 4d quantum gravity with negative cosmological constant in the minisuperspace approximation to see if pure Einstein gravity suffices to reproduce the S 3 partition function of ABJM theory.…”
Section: Jhep06(2018)106mentioning
confidence: 93%
See 2 more Smart Citations
“…Although it has been demonstrated that (1.1) can be reproduced by the supergravity localization [15], we wish, in particular, to show that the emergence of the Airy function is not all due to the sophistications of supergravity and extra dimensions but rather lies at the core of 4d quantum gravity. Motivated by the appearance of Airy functions in quantum cosmology [16,17], we study 4d quantum gravity with negative cosmological constant in the minisuperspace approximation to see if pure Einstein gravity suffices to reproduce the S 3 partition function of ABJM theory.…”
Section: Jhep06(2018)106mentioning
confidence: 93%
“…In contrast to N = 4 SYM on S 4 , the S 3 partition function of ABJM theory receives nontrivial 1/N corrections dual to quantum gravity all loop perturbative effects and, remarkably, it sums up to an Airy function [8,9]. Furthermore, the Airy function has been reproduced as the quantum gravity partition function of M-theory on AdS 4 times Sasaki-Einstein seven manifolds by the supergravity localization computation [15]. The goal of this section is to go beyond the large N /classical limit of (3.1).…”
Section: The S Partition Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…The projection condition (4.7) then implies 45) which are equivalent to (3.10). The projection condition (4.7) also constrains the number of fermionic operators in a way similar to (3.12).…”
Section: Usp(2n ) Internal Symmetrymentioning
confidence: 99%
“…Along the line of the interpretation in the gravity dual, it is very interesting to note that the coefficient of the one-loop log term was studied from the gravity side [67] and the match with the expansion of the Airy function (1.1) was found. Also, very recently, the Airy function was reproduced from the localization computation in the gauged supergravity [68]. Finally, though we have used the matrix model (2.2) obtained after localization for the partition functions of superconformal Chern-Simons theories, it would be interesting to study the non-perturbative instanton effects directly from the field-theoretical viewpoints.…”
Section: Jhep11(2014)164mentioning
confidence: 99%